2014
DOI: 10.2527/jas.2014-7711
|View full text |Cite
|
Sign up to set email alerts
|

Selection for residual feed intake in growing pigs: Effects on sow performance in a tropical climate1,2

Abstract: The aim of the study was to evaluate the consequences of a divergent selection for residual feed intake (RFI) during growth in a temperate environment (TEMP) on sow performance in a tropical environment (TROP). Sows came from a selection experiment conducted at INRA in which 2 lines were selected for larger (RFI(+)) or smaller (RFI(─)) feed intake than predicted from performance. In the first analysis, a subsample of data obtained in TROP conditions (49 lactations) was compared to those obtained in TEMP on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 30 publications
0
9
0
3
Order By: Relevance
“…To our knowledge, this is the first estimated heritabilities obtained in pig. In a study on lactating sows produced from lines divergently selected for residual feed intake, Renaudeau et al (2014) reported that Figure 2 Heritability (h 2 ) for rectal temperature (RT), cutaneous temperature (CT), respiratory rate (RR) at 0700 and 1200 h, and daily feed intake as a function of days of lactation in Large White sows reared in tropical humid conditions. σ 2 a = direct additive genetic variance; σ 2 c = permanent environmental variance of the sow; σ 2 e = residual variance; h 2 = heritability; r = repeatability; ADFI = average daily feed intake; BWc = % of change of BW of the sow during lactation; LBWg = litter BW gain; RT = rectal temperature; CT = cutaneous temperature; RR = respiratory rate.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To our knowledge, this is the first estimated heritabilities obtained in pig. In a study on lactating sows produced from lines divergently selected for residual feed intake, Renaudeau et al (2014) reported that Figure 2 Heritability (h 2 ) for rectal temperature (RT), cutaneous temperature (CT), respiratory rate (RR) at 0700 and 1200 h, and daily feed intake as a function of days of lactation in Large White sows reared in tropical humid conditions. σ 2 a = direct additive genetic variance; σ 2 c = permanent environmental variance of the sow; σ 2 e = residual variance; h 2 = heritability; r = repeatability; ADFI = average daily feed intake; BWc = % of change of BW of the sow during lactation; LBWg = litter BW gain; RT = rectal temperature; CT = cutaneous temperature; RR = respiratory rate.…”
Section: Resultsmentioning
confidence: 99%
“…No literature was found to compare with our estimated correlations between ADFI and RR. Renaudeau et al (2014) studied thermoregulation responses in tropical conditions of lactating sows from two divergent lines for residual feed intake. This study showed that ADFI and RR in the line selected for high residual feed intake were higher than in the line selected for low residual feed intake (+590 g/day and +8 breaths/min, respectively).…”
Section: Resultsmentioning
confidence: 99%
“…In the ISU lines, a significant decrease of ADG was reported in the low RFI line compared with the high RFI line, and similar to the INRA lines, the LRFI pigs had more muscle and less fat (Young and Dekkers, 2012 ). In addition to differences in DFI, a reduced water intake as g/kg BW 0.60 per day (−33%, P =0.062) was reported in LRFI pigs (Renaudeau et al ., 2013 ).
Figure 1 Genetic trends in the divergent selection experiment for residual feed intake (RFI) on component traits and meat quality expressed in genetic standard deviations of the traits ( σ g ), obtained from a linear mixed model including an animal random effect structured by the pedigree relationship matrix.
…”
Section: Genetics Of Residual Feed Intake and Impacts On Main Dimensimentioning
confidence: 99%
“…In the sixth generation of selection for RFI, N and P excretion, evaluated by a modelling approach, was shown to be slightly reduced in LRFI pigs (4.0% and 2.4%, respectively; Supplementary Material S1, Faure et al , 2012). However, some of these differences were lower or not observed in experimental trials during short periods of time where animals were individually housed (Barea et al ., 2010 ) or exposed to stressors (Renaudeau et al ., 2013 ; Labussière et al ., 2015 ). Recent studies on the genetic relationships between feed efficiency and excretion in commercial populations allowed to quantify moderate to high genetic correlations between N excretion and feed efficiency using predictive equations ( Table 3 ; Saintilan et al ., 2013 ) or direct measurement (Shirali et al ., 2012 , 2014 ).…”
Section: Genetics Of Residual Feed Intake and Impacts On Main Dimensimentioning
confidence: 99%
“…Despite a substantial reduction in FI, an increase in carcass lipid retention has been described in chickens (Geraert et al 1996), growing pigs (Christon 1988), and lactating sows (Renaudeau et al 2014) reared under HS conditions. Increased adiposity potentially results from decreased adipose tissue mobilization, since we and others have demonstrated that HS decreases plasma NEFA concentrations in growing ruminants (Ronchi et al 1999;O'Brien et al 2010), lactating cows (Rhoads et al 2009a;Wheelock et al 2010;Baumgard et al 2011), sheep (Sano et al 1999), growing pigs (Pearce et al 2013a), chickens (Geraert et al 1996), rodents (Sanders et al 2009;Morera et al 2012), and exercising humans (Febbraio 2001); and HS cows have a blunted response to an epinephrine challenge (Baumgard et al 2011).…”
Section: Lipid Metabolismmentioning
confidence: 99%